Screening Standards in Sharia Capital Market Investor Legal Protection - Kefi Miftachul Ulum; Mohammad Khoirul Ulum (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2023)
The growth of single investor identification on September 29 2022 reached 9.76 million, dominated by millennials with a percentage of 59.43%, and when compared to the total population of Indonesia, the share of investor growth is around 3.6%. Calculation of growth recapitulation is based on account opening through Perantara Pedagang Efek (PPE) both conventionally and sharia. Investors who enter the stock exchange consist of various types who have their own goals, so they have the potential risk of codifying securities on ISSI and JII of the formation of maisir, garar, darar and causing mafsadat. This study aims to analyze the screening standards in the legal protection of Islamic capital market investors. This research is normative legal research with a breakdown of 536 sharia issuers and analyzed through industry sectoral typologies and regulations 15/POJK.04/2015 and 35/POJK.04/2017. The results of this study found 7 issuers in the technology and film sectors that passed the DES, so deficiencies in the standard screening procession need to be improved by sectoral-based screening methods in the Sharia issuer index procession to increase the application of Sharia principles.